PENGARUH SIKAP MAHASISWA PADA FISIKA DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR FISIKA DASAR MAHASISWA - Dasmo Dasmo (Faktor Exacta, 2010)
The purpose of this study to determine the influences of student’s attitudes through physics subject and motivation as the results of physical study. This study used survey methods, namely to find a clear result of the problem. Instruments that used in this study was a questionnaire about student’s attitudes to physics, study motivation and results of physical study, each of them which amounted to 20 questions, 20 questions and results of physical study took from score at middle in a semester. The data obtained will be analyzed using path analysis. This study gives the following results: 1) Student’s attitudes to physics are not given directly to the results of physical study. This  way looked from score coefficient correlation between X1 and Y is 0,116 and coefficient get effect (P31) is (-0,0378). Negative score was showed that means three is no positive effects and significant value between attitudes of students through physical subject Student’s attitude through physical subject with its score. In the other hand, students who have positive attitude with Physical subject at Technical Informatics program, as the result it is not give effect to the test score. 2) Learning motivation gives effects directly with result of study at students’ basic physic subject. It is showed by coefficient value of correlation between X2 and Y is 0,678 and coefficient get effect (P32) as 0,686. Positive value, it’s showed that means there is a positive effect and significant value between students learning motivation through result of study at basic physic subject. This positive result gives meaning that students who get high motivation so get high score also. This result have enough proved that learning motivation is so important and it’s really effected in learning process. 3) students’ attitude in physic gives effect negative indirectly through result of study at basic physic subject through learning motivation. This things is showed by coefficient value on correlation. It is showed by between X1 and Y is 0,116 and coefficient value get effect (P31) is -0,0378, also coefficient correlation between X1 and X2 is 0,224 and coefficient get effect (P21) is 0,224 so coefficient is not give effect directly between X1 to Y X2 through with multiple P31.P21 = (-0,0378)(0,224) = -0,008467. Seeing the negative signs from the result above, the value means that there is no significant positive effect directly between student’s attitude at basic physical subject through students’ learning motivation. This results gives information that student’s positive attitude from students at Technical Informatics students to basic physical subject will not give effect to their result of study through learning motivation. Keywords: student’s attitudes, motivation, physics, path analysis